Analysis of Pilotage Service Time Trends at Terminals in the Surabaya’s West Shipping Channel - Zain, Riza Rosali; Sulistyo, Juny Andry; Sumirin, Sumirin (ASTONJADRO, 2026)
This study analyzes the trend of Waiting Time for Pilot (WTP) and Approach Time (AT) as the main indicators of pilotage service performance at terminals in the Surabaya’s West Shipping Channel (APBS). The data used comes from the monthly monitoring report of PT Pelindo Regional 3 in 2023, which includes Gresik Terminal, Jamrud Terminal, Nilam Mirah Terminal, Teluk Lamong Tanjung Perak Terminal, and Kalimas Terminal. The research method uses a descriptive-quantitative approach with a comparative analysis of actual achievements against the Corporate Work Plan and Budget (RKAP) targets. The results show that all terminals, except Teluk Lamong Terminal, managed to maintain an average WTP well below the RKAP standard of 0.50 hours, with the best performance shown by Gresik Terminal (0.04 hours). In terms of AT, Jamrud and Nilam Mirah Terminals recorded better achievements than the RKAP, Teluk Lamong Terminal was relatively on target, while Gresik Terminal showed a negative deviation with AT exceeding the RKAP target. The anomalous WTP spike at Teluk Lamong Terminal in August (5 hours) is an important note that needs to be anticipated in operational planning. This study concludes that pilotage efficiency at APBS is very good in terms of WTP, but there is still room for improvement in the AT aspect. The use of digital technologies such as Vessel Traffic Service (VTS) and E-Pilotage is recommended as a strategy to improve the consistency of pilotage performance in the future.